1999
DOI: 10.1046/j.1439-0507.1999.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of plant extracts against dermatophytes

Abstract: The aqueous extracts (15 micrograms ml-1 medium) of 22 plants used in folkloric medicine in Palestine were investigated for their antifungal activity and minimum inhibitory concentrations (MICs) against nine isolates of Microsporum canis, Trichophyton mentagrophytes and Trichophyton violaceum. The extract of the different plant species reduced colony growth of the three dermatophytes by 36 to 100% compared with the control treatment. Antimycotic activity of the extract against the three dermatophytes varied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(125 citation statements)
references
References 41 publications
6
112
0
7
Order By: Relevance
“…The similar to that from the work of Ali-Shtayeh and Abu-Ghdeib (1999), who reported that aqueous extracts of 22 plants recorded wide variations in their MIC values against Microsporum canis, Trichophyton mentagrophytes and Trichophyton violaceum. This could be attributed to the variations in the phytochemical properties of the plants and differences among the fungal species.…”
Section: Resultssupporting
confidence: 89%
“…The similar to that from the work of Ali-Shtayeh and Abu-Ghdeib (1999), who reported that aqueous extracts of 22 plants recorded wide variations in their MIC values against Microsporum canis, Trichophyton mentagrophytes and Trichophyton violaceum. This could be attributed to the variations in the phytochemical properties of the plants and differences among the fungal species.…”
Section: Resultssupporting
confidence: 89%
“…Namely, the methanol extracts were most active in comparison with acetone and ethyl acetate extracts. The greater effectiveness of the methanol extracts resulted from the fact that methanol is a very useful solvent capable of extracting a wide range of compounds [26]. Weak antimicrobial activity was observed in the extracts of T. botrys, which showed a low total phenolic content.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts and their essential oils are one of several non-synthetic chemical control options that have recently received attention for controlling plant diseases (Soylu et al 2005;Abad et al 2007). The methanolic extract of fenugreek was potent in inhibiting dermatophytes and Candida albicans (Shtayeh and Abu Ghdeib 1999;Olli and Kirti 2006). Extracts of harmal seeds and roots were found to contain a mixture of active alkaloids, and among these harmaline was the most active antifungal agent (Telezhenetskaya and Dyakonov 2004).…”
Section: Introductionmentioning
confidence: 99%